Let me be me [videorecording (DVD)] - Crane, Dan; Greenberg, Jackson; Westphal, Kyle (Greenwich Entertainment, 2022)
When the Westphal family learned that their six-year-old Kyle was on the Autism spectrum, they feared they might never develop a real connection to their child. Withdrawn and constantly wrapping himself in fabric and blankets, Kyle was retreating from the world around him. Determined to find a way to connect, his parents embarked on an intense and radical journey that involved compassionately joining Kyle in his unique behaviors. Twenty years later, the entire family looks back at Kyle's journey with candor and humor. It reveals what happens when a boy who used fabric as his shield to hide grows up to become a fashion designer, forging connections with friends and family along the way.